Adherence to a Web-based Exercise Programme: A Feasibility Study Among Patients with Hip or Knee Osteoarthritis - Kenth-Louis Joseph; Hanne Dagfinrud; Kåre Birger Hagen; Kristine Røren Nordén; Camilla Fongen; Ole-Martin Wold; Rana S. Hinman; Rachel K. Nelligan; Kim L. Bennell; Anne Therese Tveter (Medical Journals Sweden, 2023)
Objectives: To describe adherence to a 12-week web-based aerobic exercise programme, to compare characteristics between those who adhere or not, and to identify barriers for exercising in patients with hip or knee osteoarthritis. Design: Single-arm feasibility study. Subjects: Patients with hip or knee osteoarthritis in specialist healthcare, age 40-80 years, and not candidates for joint surgery. Methods: Adherence to a 12-week exercise programme was defined as having completed ≥ 2 exercise sessions a week for at least 8 weeks. Baseline differences between adherent and non-adherent groups in demographics, symptoms, disability, physical activity and fitness were assessed using Mann-Whitney U or χ2 tests. Reasons for not completing exercise sessions were reported in weekly diaries.  Results: A total of 29 patients (median age 64 years, 72% female) were included. Median baseline pain (numerical rating scale 0-10) was 5. Fifteen patients adhered to the exercise programme, 14 did not. Non-adherent patients were less active (p = 0.032) and had lower cardiorespiratory fitness (p = 0.031). The most frequently reported barrier to exercising was sickness. Less than 10% reported pain as a barrier. Conclusion: Half of the patients with hip or knee osteoarthritis adhered to the digitally delivered exercise programme and the most frequently reported barrier for adherence was sickness, while less than 10% reported pain as a reason for not exercising. Trial registration: ClinicalTrials.gov, NCT04084834. The Regional Committee for Medical and Health Research Ethics South-East, 2018/2198.